Electroconvulsive therapy: Knowledge and attitudes among medical interns and the general public - Bilal Ahmad Bhat; Shabir Ahmad Dar; Arshad Hussain; Rouf Ahmad Mir (Wolters Kluwer Medknow Publications, 2020)
Background: Negative view of electroconvulsive therapy (ECT) is held not only by the general public but also by the medical professionals. Aims: The study aims to assess knowledge of ECT and attitude toward it in medical interns and general public. Materials and Methods: This was a cross-sectional study in which knowledge of ECT and attitude toward this treatment was assessed in medical interns and general public using ECT knowledge and attitude questionnaire. A total of 36 participants from each group were included in the study. Results: Among the medical interns, 75% reported the source of information as medical books, whereas in general public, 88.9% reported the primary source of information as media. Our participants, from both groups, were more knowledgeable about the consent, side effects, and procedure part of the questionnaire compared to other parts of it. The mean score for knowledge questionnaire was 16.58 ± 4.78 and 9.94 ± 4.82 for medical interns and general public, respectively (t = 3.74; P = 0.001). The mean score on attitude questionnaire was 9.94 ± 4.82 and 0.83 ± 8.56 for medical interns and general public, respectively (t = 5.56; P = 0.0001). In both medical interns and general public, the total score on knowledge questionnaire and total score on attitude questionnaire were correlated positively (rs = 0.542, P < 0.001 and rs = 0.446, P < 0.006, respectively). Conclusion: Our study found a low knowledge of ECT in general public with less favorable attitude toward this treatment. With a good knowledge of ECT and more favorable attitude in medical students, still there are lacunae in them. However, in both these groups, there was a positive correlation between knowledge and favorable attitude.